Knowledge representation for missing persons investigations. Issue 1 (13th March 2017) - Taylor, Mark; Reilly, Denis
Abstract : Purpose: This paper aims to present the application of situation calculus for knowledge representation in missing persons investigations. Design/methodology/approach: The development of a knowledge representation model for the missing persons investigation process based upon situation calculus, with a demonstration of the use of the model for a missing persons example case. Findings: Situation calculus is valuable for knowledge representation for missing persons investigations, as such investigations have state changes over time, and due to the complexity of the differing investigation activities applicable to different situations, can be difficult to represent using simpler approaches such as tables or flowcharts. Research limitations/implications: Situation calculus modelling for missing persons investigations adds formalism to the process beyond that which can be afforded by the current use of text, tables or flowcharts. The additional formalism is useful in dealing with the uncertainty present in such investigations. Practical implications: The implications are a simplification of the application of the current police guidelines, and thoroughness in the application of such guidelines for missing persons investigations via situation calculus modelling. Social implications: This paper supports the management of missing person investigations, by using the most critical variables in a missing persons investigation to determine relevant investigation and search activities applicable to the circumstances of a given case. Originality/value: The novelty of the knowledge representation approach is the application of situation calculus via state and action vectors and a matrix of fluents to the process of missing persons investigations.